2007
DOI: 10.3892/or.17.4.865
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in peripheral blood mononuclear cells after whole body irradiation

Abstract: Telomerase activity in vitro represents a radiationinducible function. To test this effect after irradiation in vivo, we measured telomerase activity in peripheral blood mononuclear cells (PBMC) of 25 patients with leukemia or lymphoma before and 1 h after whole body irradiation. Telomerase activity of the patients was compared to telomerase activity in PBMC of 15 healthy volunteers. Peripheral blood of the patients was taken before and 1 h after the first fraction of whole body irradiation (2 Gy). Blood sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Similar results were reported by Finnon et al (24), albeit in mouse cells, and by Leteurtre et al in AML-driven cell line (29). In contrast, an up-regulation of TA after irradiation was reported in peripheral blood mononuclear cells after mitogen stimulation and in hematopoietic cell lines (30). Interestingly, the group of Xing et al found that lymphocytes from normal controls did not activate telomerase after ex vivo irradiation, whereas lymphocytes isolated from patients with bladder and lung cancers exhibited telomerase activation (17).…”
Section: Discussionsupporting
confidence: 67%
“…Similar results were reported by Finnon et al (24), albeit in mouse cells, and by Leteurtre et al in AML-driven cell line (29). In contrast, an up-regulation of TA after irradiation was reported in peripheral blood mononuclear cells after mitogen stimulation and in hematopoietic cell lines (30). Interestingly, the group of Xing et al found that lymphocytes from normal controls did not activate telomerase after ex vivo irradiation, whereas lymphocytes isolated from patients with bladder and lung cancers exhibited telomerase activation (17).…”
Section: Discussionsupporting
confidence: 67%
“…Telomerase is known to be a ribonucleoprotein in human cells that exhibits reverse transcriptase activity ( 11 ). Telomerase contains an RNA component to provide a template for the synthesis of repeated telomeric sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Currently used techniques include the isolation of cancer cells from within the blood, magnetic bead separation (2)(3)(4)(5) and density-gradient centrifugation (6)(7)(8)(9); however, these are subject to problems associated with cost and operability. With regard to clinical applications, great demands are placed on devices that can be sterilized.…”
Section: Introductionmentioning
confidence: 99%